Pendidikan Inklusi bagi Anak Berkebutuhan Khusus dalam Perspektif Epistemologi Islam - Hasan Baharun; Robiatul Awwaliyah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2018)
This paper presents the conception of inclusive education in the perspective of Islamic epistemology. Education is a process of the child that lasts until the child reaches a mature adult. To achieve that every child is entitled to a good education, not to mention children with special needs. History shows that over the centuries in all countries of the world, individuals who are different from most other individuals are always denied presence by society. This is due to the assumption that members of the disabled group may not be able to contribute to the group. Those who are different because they have disabilities, are excluded, do not get the touch of affection and meaningful social contacts are not even acknowledged their existence. The government is in the midst of inclusive education, in which inclusive education is able to place all children (normal children and special needs children) in a community that is an attempt not to separate them from the normal society. To provide a deeper understanding of the source of inclusive education, this paper will present the inclusion education in the globe of Islamic Epistemology which is one branch of philosophy and examines the estuary of a knowledge in which inclusive education. By understanding the source of inclusive education it is hoped that the belief in the importance of inclusion education is stronger.